Peritoneal carcinomatosis management through cytoreductive surgery with hyperthermic intraperitoneal chemotherapy: first experience in Iraq - Mahmood, Aqeel Shakir; Al-Obaidi, Ahmed Dheyaa; Al-Obaidi, Mustafa Najah; Madlul, Yousif Ali; Al Sakini, Ahmed Sermed; Hashim, Hashim Talib; Shakir, Ahmed A.; Qassim, Tabarak; Ahmed Shimal, Aya; Ahmed, Marafi Jammaa; Mohammed, Fatima Elbasri Abuelgasim; Al-Obaidi, Hasan (Frontiers in Oncology, 2026)
BackgroundGiven the current lack of data from Iraq regarding peritoneal carcinomatosis (PC) management using Cytoreductive Surgery (CRS) with Hyperthermic Intraperitoneal Chemotherapy (HIPEC), and the diversity in genetics, environmental conditions, and socioeconomic factors in Iraq, we conducted the first study of PC management using CRS+HIPEC.MethodsThis is a retrospective single-center study at Al-Arabi Private Hospital in Baghdad, Iraq, on 61 patients recently diagnosed with peritoneal cancer who have been managed by CRS and HIPEC for the first time in Iraq. Subsequently, the patients were observed for a duration of 4 years throughout the follow-up phase.ResultsThe study, with an average participant age of 49.15 years and females representing 62%, showed an overall survival rate of 26.2% and a median survival duration of 32.51+/-12.8 months. Colorectal and ovarian cancers were predominant at 49% and 21%, respectively. The closed method of HIPEC was used in 80% of cases. Significant associations were found between Neoadjuvant Chemotherapy (NACT) (p = 0.0001), Cytoreductive Surgery score (CC score) (p = 0.01), Peritoneal Cancer Index (PCI) (p = 0.001), and survival rates.ConclusionIn summary, as Iraq’s first study, our study provides crucial insights into PC management. Highlighting the vital role of NACT in CRT+HIPEC treatment, our study reveals no statistically significant difference between closed and open HIPEC methods. Our study further emphasizes the prognostic value of an elevated PCI and the critical importance of optimal cytoreduction, as reflected in the Completeness of Cytoreduction (CC) score. Our findings call for continued research, collaboration, and practical application to advance PC care.